Hubungan Intensitas Menonton Tayangan Kekerasan di Televisi dan Intensitas Pemberian Punishment dengan Perilaku Bulyying di Kalangan Pelajar SMA - Suprihatin, Bambang (Universitas Ahmad Dahlan, 2012)
AbstractÂ Bullying is an aggression act that goal to hurt, humiliate and coercion a weak victim psychologically and physicaly. The present study aims to examine the role of watching violent movie in televesion, and punishment reinforcement with bullying behavior among senior high school students. 128 students were involved in this study. The result showed that there is a relationship between watching violent movie in television and punishment reinforcement with bullying behavior. The implication of the study is discussed further in article.Keywords: intensity watching violent movie in television, punishment reinforcement and Â bullying behavior.Â